Tradisi Mangongkal Holi sebagai Penegasan Identitas Suku Batak - Cristianingsih, Antonia; Elan, Anjelita; Agnesia, Desima Erlinda; Mulyatno, Carolus Borromeus (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The Toba Batak community resides in various regions of Indonesia, yet they share traditions that unite their identity as Batak people. One such emblem of unity is the Mangongkal Holi tradition. The purpose of this research is to describe the Mangongkal Holi ceremony as an expression to affirm the identity of the Toba Batak people. The method employed to gather data for this study was through literature review. Three essential questions served as instruments in this research. First, what is the significance of the Mangongkal Holi ceremony? Second, how and when is this ceremony conducted? Third, what is the meaning behind this ceremony? The research findings reveal that despite the dispersion of Toba Batak people across different regions, after the passing of their relatives, they bring the ancestral bones to be unified at a place called the Monument. The process of collecting these bones at a monument is referred to as Mangongkal Holi. This ceremony is conducted based on family agreements, considering this tradition as a means of reunion among families. The ceremony holds significance as a gesture of reverence to the ancestors and as a symbol of kinship.AbstrakMasyarakat Batak Toba hidup tersebar di berbagai wilayah Indonesia, namun ada tradisi yang menyatukan identitas mereka sebagai orang Batak. Salah satu tanda kesatuan tersebut adalah tradisi Mangongkal Holi. Tujuan dari penelitian ini adalah untuk mendeskripsikan upacara Mangongkal Holi sebagai ungkapan untuk menegaskan identitas orang batak. Metode yang digunakan untuk mengumpulkan data-data penelitian ini adalah melalui studi Pustaka. Tiga pertanyaan penting yang menjadi instrumen dalam penelitian ini. Pertama, apa yang dimaksud dengan upacara Mangongkal Holi? Kedua, bagaimana dan kapan upacara ini dilaksanakan? Ketiga, apa makna dari upacara ini? Hasil penelitian menunjukkan bahwa meskipun orang Batak Toba tersebar di berbagai daerah, namun setelah meninggal para kerabatnya membawa tulang-tulang leluhur mereka untuk disatukan di tempat yang disebut Tugu. Proses pengumpulan tulang-tulang di sebuah tugu itulah yang disebut sebagai Mangongkal Holi. Upacara ini dilaksanakan sesuai kesepakatan keluarga mengingat tradisi ini sebagai sarana perjumpaan antar keluarga. Upacara ini memiliki makna sebagai upaya penghormatan kepada para leluhur dan tanda kekeluargaan.